SAS DRAKENSBERG’S FIRST 25 YEARS: THE LIFE AND TIMES OF THE SA NAVY’S FOREMOST GREY DIPLOMAT, 1987–2012 - Wessels, Andre (Scientia Militaria - South African Journal of Military Studies, 2013)
The South African Navy (SAN)’s first (and thus far only) purpose-built combat support ship, SAS Drakensberg, was commissioned on 11 November 1987. In this study, the ship’s first 25 years of service (1987–2012) to the SAN (and the people of South Africa) was analysed, with special reference to her role as a grey diplomat (i.e. the flag-showing cruises she undertook and her concomitant role in strengthening diplomatic and other ties with many countries). The Drakensberg’s other peace-time roles were also be reviewed, including – – humanitarian and related relief expeditions; – her role during exercises with other SAN warships as well as ships and submarines from other navies, both in South African waters and across the globe; – her role as a training ship; – ceremonial duties; and – lately also in anti-piracy patrols. Throughout the study, the Drakensberg’s activities were evaluated against the background of the changing political and other developments in South Africa, as well as internationally. In the article, it will be indicated how and why a ship that was conceived, designed and built in the apartheid era, in due course became the most prominent, most visible and most successful warship that thus far has been in SAN service.